2018
DOI: 10.2214/ajr.17.18436
|View full text |Cite
|
Sign up to set email alerts
|

Downgrading and Upgrading Gray-Scale Ultrasound BI-RADS Categories of Benign and Malignant Masses With Optoacoustics: A Pilot Study

Abstract: Optoacoustic ultrasound resulted in BI-RADS category downgrading of benign masses and upgrading of malignant masses compared with gray-scale ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The dual mode PA US imaging technology can potentially improve specificity in differentiating between malignant and benign breast masses, which can reduce the number of benign breast mass biopsies as well as false-positive examinations. Neuschler et al [112] performed a multicenter in vivo study with their dual mode PA-US imaging system on 94 breast masses. They found that the dual mode system showed 7.9% improvement in specificity compared to their US imaging system, whereas the sensitivities of both PA-US, as well as only the US system, were 97.1%.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The dual mode PA US imaging technology can potentially improve specificity in differentiating between malignant and benign breast masses, which can reduce the number of benign breast mass biopsies as well as false-positive examinations. Neuschler et al [112] performed a multicenter in vivo study with their dual mode PA-US imaging system on 94 breast masses. They found that the dual mode system showed 7.9% improvement in specificity compared to their US imaging system, whereas the sensitivities of both PA-US, as well as only the US system, were 97.1%.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…[1][2][3][4][5][6] For breast cancer diagnosis, one promising technique is OA imaging combined with ultrasound (OA/US). [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Combining OA with ultrasound is advantageous because each modality provides information that is complementary to the other. Structural and functional information pertaining to total hemoglobin concentration (c tHb ) and blood oxygen saturation (s O 2 ) can be visualized with OA, while morphological and anatomical information can be obtained with ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] Since OA directly visualizes c tHb and s O 2 , this can potentially give clinicians the ability to perform more accurate diagnosis. [7][8][9][10][11][12][13][14][15] In OA/US, the probe also acquires conventional ultrasound images, which are coregistered and displayed simultaneously with OA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations